'There's a star man waiting in the sky': How does public radio approach under-the-radar musicians in the United Kingdom and Spain?. (1st April 2017) - Costa Gálvez, Lola
The present article aims to address one specific issue concerning public service media: how does public radio approach under-the-radar musicians? Throughout its history public radio has continued to discover and support upcoming musicians, who, by definition, have few promotional opportunities due to their position on the periphery of the music industry. This research is developed by comparing various public radio initiatives regarding under-the-radar musicians in the United Kingdom and Spain at national and regional level. Within the framework of comparative media systems, it provides case studies of BBC Introducing (BBC Radio, United Kingdom), Sona9 (CCMA, iCat.cat, Catalonia, Spain), Maketa Lehiaketa (EITB, Gaztea Irratia, Basque Country, Spain) and Proyecto Demo (RTVE, Radio 3, Spain). This subject is approached by using a mixed methodology of content analysis and interviews. The findings elucidate how these initiatives are based upon a strong public service commitment, through the combination of public service media and live venues, with particular relevance to young local music scenes and the national music industry. It is concluded that providing support to under-the-radar musicians could be a valuable lifeline for public service broadcasting in seemingly permanent crisis.